The difference in risk of chronic pulmonary disease morbidity and mortality between elite athletes and ordinary men in Finland - Kontro, T. K.; Sarna, S.; Kaprio, J.; Kujala, U. M. (European Journal of Sport Science, 2020)
Introduction: The impact of a history of competitive sports on later smoking behavior and occurrence of chronic pulmonary diseases is poorly known. We investigated how a history of elite level sports predicted later pulmonary disease morbidity and mortality.